The Right to Know: First Amendment Overbreadth - Walter Gellhorn (Washington University Law Quarterly, 1976)
Professor Emerson’s lecture on “Legal Foundations of the Right to Know” keynoted a daylong symposium on the First Amendment held March 3, 1976, at Washington University. At a subsequent panel discussion several distinguished lawyers and members of the press responded to Professor Emerson's address. The remarks of two panel members, Professor Walter Gellhorn and Mr. James C. Goodale, are reprinted below. Transcripts of their responses have been edited slightly for publication.
Keywords: First Amendment law